DEVELOPMENT OF MONOPOLY BOARD MEDIA ON THEME OF EVENTS IN LIFE CLASS V SDN MANDALAWANGI 2 - Desi Utari; Zerri Rahman Hakim; Damanhuri (Sekolah Tinggi Keguruan dan Pendidikan Syekh Manshur, 2023)
This study aims to develop monopoly media on the theme of events in life and determine the feasibility of the developed media. In this study using the R&D research method on the Brog and Gall development design which has been modified by Sugiyono which includes 6 stages such as: 1) Problem analysis; 2) Data collection; 3) Product design; 4) Validation ah;I; 5) Design revision; 6) Product trials. This research was conducted in class V SDN Mandalawangi 2. Based on the feasibility results that had been carried out by a team of experts such as media experts, material experts and language experts. The results of research conducted by media experts obtained an average score of 89% in the